Análise e modelagem de conflito pelo uso da água: o caso da região hidrográfica do médio Jaguaribe, Ceará, Brasil - Cavalcante, Renata Rochelly de Mesquita (2024)
The research formally and systematically modeled the actual conflict of Water Allocation in the Castanhão Reservoir, located in the Middle Jaguaribe Hydrographic Region, northeastern Brazil. To achieve this, the conflict Graph Model for Conflict Resolution (GMCR+) by HIPEL et al., 2014 was employed. The conflicts present in the study area were identified through a documentary analysis of the meetings’ transcriptions of the Hydrographic Basin Committee. Documents from the year 2004 to 2021 were chosen, as the main reservoir of the Middle Jaguaribe Hydrographic Basin – MJHB, the Castanhão Reservoir, started operations in 2004. After the survey, these documents were classified according to the typology proposed by Studart et al. (2021). Ninety minutes of the Committee's meetings transcriptions from 2004 to 2021 were analyzed, revealing 111 conflicts. In the application of GMCR+, 100 viable options were identified, and using stability criteria, three equilibrium states were determined. The game analysis was conducted through a unilateral game and by forming three coalitions. The conflict analysis through coalition formation suggests that the parties can collaborate in seeking a solution to the conflict.